Perbedaan Pendekatan dalam Memperoleh Pengetahuan (Prespektif Pengetahuan Islam dan Filsafat Barat) - Waluyo; Muflihah Istiana; Ressa Ananda Putra; Fiki Fakhrina Mafazatur Rahmah (Interdisciplinary Explorations in Research Journal, 2024)
This study aims to examine the philosophy of science through Islamic epistemology, encompassing theories, concepts, and sources of knowledge. The research employs a library research method with a qualitative approach. Throughout the history of the philosophy of science, two central issues have been the focus: the criteria of scientific validity and the development of knowledge. Various schools of thought in the philosophy of science that seek truth include Rationalism, Empiricism, Positivism, and others. In the Islamic tradition, knowledge must achieve certainty, requiring multiple sources such as explanation, reason, and experience to fulfill the elements of truth. The types of Islamic epistemology in the realm of knowledge include Bayani, Burhani, and Irfani. The collaboration or similarities shared among sciences in the philosophy of science and epistemology can be observed in the alignment of Bayani with Positivism, Burhani with Rationalism, and Irfani with Empiricism. This study is expected to assist in understanding the sources of knowledge and the schools of thought in the pursuit of truth.